2005
DOI: 10.1152/ajprenal.00069.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sympathetic nerves and angiotensin II on renal sodium and water handling in rats with common bile duct ligature

Abstract: . Effects of sympathetic nerves and angiotensin II on renal sodium and water handling in rats with common bile duct ligature. Am J Physiol Renal Physiol 288: F1267-F1275, 2005. First published February 8, 2005 doi:10.1152/ajprenal.00069.2003.-We tested the hypothesis that angiotensin II is likely to be mandatory for the neurogenic sodium and volume retention in cirrhotic rats with common bile duct ligature (BDL) following an acute volume load. To assess the neural control of volume homeostasis, 21 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…Renal cortical tissue extraction and real-time RT-PCR were carried out as described (35). Briefly, first-strand cDNA was synthesized with TaqMan reverse transcription reagents (Applied Biosystems, Darmstadt, Germany) using random hexamers as primers.…”
Section: Methodsmentioning
confidence: 99%
“…Renal cortical tissue extraction and real-time RT-PCR were carried out as described (35). Briefly, first-strand cDNA was synthesized with TaqMan reverse transcription reagents (Applied Biosystems, Darmstadt, Germany) using random hexamers as primers.…”
Section: Methodsmentioning
confidence: 99%
“…Renal cortical tissue extraction and real-time RT-PCR were carried out as described [16]. Briefly, first-strand cDNA was synthesized with TaqMan reverse transcription reagents (Applied Biosystems, Darmstadt, Germany) using random hexamers as primers.…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral or unilateral flank incisions were made, and renal denervation was performed by surgically stripping the renal arteries and veins of adventitia, cutting all visible renal nerve bundles under a dissection microscope (ϫ25), and coating the vessels with a solution of 10% phenol in 95% ethanol as described previously. 31 The bilateral renal denervation procedure prevents the renal vasoconstrictor response to suprarenal lumbar sympathetic nerve stimulation and prevents the antinatriuretic response to environmental stress. It can be demonstrated that this procedure reduces renal catecholamine immunofluorescence to nondetectable levels and reduces renal tissue norepinephrine concentration to Ͻ5% of control.…”
Section: Rat Model Of Anti-thy-11 Nephritismentioning
confidence: 99%